Kinetics and Equilibrium Properties of Cu(II) Adsorption Using Modified Activated Carbon from Empty Oil Palm Fruit Bunches - Br Manik, Trivena Myta; Ramadhan, Dwi Sapri; Faradilla, Putri; Rahmah, Siti; Selly, Rini; Jasmidi; Zubir, Moondra (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Oil palm empty fruit bunch (EFB) is a biomass waste containing lignocellulose that has the potential to be used as activated carbon to adsorb heavy metals such as Cu(II). This study aims to compare the adsorption performance of Cu(II) ions from three types of TKKS-based adsorbents, namely pure activated carbon (A.C), Fe-Cu metal modified activated carbon (A.C-Fe-Cu), and activated carbon composite with Cu(TAC)₂ (A.C-Cu(TAC)₂). Data were obtained from two previous studies and analyzed using first- and second-order pseudo-kinetic models, as well as Langmuir and Freundlich isotherm models. Results showed that all adsorbents followed a two-order pseudo-kinetic model with R² ≥ 0.998, indicating a chemisorption mechanism. A.C-Fe-Cu showed the highest maximum adsorption capacity (389.47 mg/g) and the best fit to both isotherm models, while A.C-Cu(TAC)₂ showed suboptimal results. Thus, the modification of TKKS with Fe-Cu metal synergistically increases the effectiveness of adsorption on Cu(II) ions and has potential for wastewater treatment applications.